2014
DOI: 10.1074/jbc.m114.611707
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Activation of Antithrombin by Heparin Involves an Altered Exosite Interaction with Protease

Abstract: Background: Exosites are known to mediate heparin allosteric activation of antithrombin. Results: Mutagenesis revealed that an exosite differentially contributes to antithrombin reactivity with factors Xa/IXa in unactivated and heparin-activated states. Conclusion: Heparin allosteric activation of antithrombin results from alterations in an exosite interaction with protease induced by core conformational changes. Significance: The findings support our recently proposed model of antithrombin allosteric activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
3
38
0
Order By: Relevance
“…In contrast, AT I207T exhibited a modest increase in inhibition stoichiometry that was more predominant in heparin-catalyzed reactions. Heparin vastly accelerates the rates of thrombin and fXa inactivation by AT; however, it also moderately promotes the substrate pathway of the branched mechanism (8), and the findings of Á guila et al (3) are consistent with this. AT I207A, which was created for comparison, behaved largely as a substrate with both proteinases but with still measurable inhibitory activity.…”
supporting
confidence: 79%
“…In contrast, AT I207T exhibited a modest increase in inhibition stoichiometry that was more predominant in heparin-catalyzed reactions. Heparin vastly accelerates the rates of thrombin and fXa inactivation by AT; however, it also moderately promotes the substrate pathway of the branched mechanism (8), and the findings of Á guila et al (3) are consistent with this. AT I207A, which was created for comparison, behaved largely as a substrate with both proteinases but with still measurable inhibitory activity.…”
supporting
confidence: 79%
“…The dissociation constant of these variants was lower than control antithrombin (Table 2). This suggested that the mutations caused a slight activation of the inhibitor in the absence of heparin, a finding observed with other antithrombin variants (6).…”
Section: Heparin Affinity Of I207t and I207a Variantsmentioning
confidence: 68%
“…Heparin activates antithrombin by two mechanisms. In one mechanism, heparin serves as a polysaccharide bridge to promote the encounter between protease and antithrombin, whereas in the second mechanism, the serpin is activated through conformational changes, which enhance reactivity with protease and involve several exosite interactions (3)(4)(5)(6). The first mechanism is dominant with the protease, thrombin, and the second selectively enhances antithrombin reactivity with factor Xa and factor IXa.…”
mentioning
confidence: 99%
“…5). FXa interacts directly with AT at a specific exosite exposed on binding to heparin (Izaguirre et al, 2014). In addition, in the presence of calcium, a single heparin chain can bind to both AT and FXa directly, enhancing the AT-FXa interaction further (Rezaie and Olson, 2000;Lin et al, 2001), but it is not an absolute requirement.…”
Section: A Antithrombin-mediated Inhibition Of Factor Iia (Thrombin)mentioning
confidence: 99%